2012
DOI: 10.1673/031.012.4601
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in the Thiamethoxam Resistant and Susceptible B-biotype Sweetpotato Whitefly,Bemisia tabaci

Abstract: Thiamethoxam has been used as a major insecticide to control the B-biotype sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). Due to its excessive use, a high level of resistance to thiamethoxam has developed worldwide over the past several years. To better understand the molecular mechanisms underlying this resistance in B. tabaci, gene profiles between the thiamethoxam-resistant and thiamethoxam-susceptible strains were investigated using the suppression subtractive hybridization (SSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
(41 reference statements)
4
17
0
Order By: Relevance
“…With whitefly development, HOT expression continued to drop to very low levels in THS adults but increased to high levels in THR adults, a finding which is in accord with the results obtained by Xie et al 13,. who used the suppression subtractive hybridization cDNA library approach.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With whitefly development, HOT expression continued to drop to very low levels in THS adults but increased to high levels in THR adults, a finding which is in accord with the results obtained by Xie et al 13,. who used the suppression subtractive hybridization cDNA library approach.…”
Section: Discussionsupporting
confidence: 92%
“…Only a few genes, e.g., cytochrome P450s and GST and ABC transporters, have been associated with thiamethoxam resistance1617. In the current study, which extends a previous study13, we cloned the full-length cDNA of HOT in B. tabaci and aligned the sequence with those of other HOT genes; the results demonstrated that the B. tabaci HOT is a classic HOT gene. The relative expression of HOT in different development stages was evaluated by qRT-PCR.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, B. tabaci resistance to neonicotinoids, especially to thiamethoxam, has been associated with elevated activities of detoxification enzymes [25], [26]. Most recently, the molecular basis of thiamethoxam resistance in B. tabaci was investigated using the suppression subtractive hybridization (SSH) cDNA library approach [27]. Based on the results of the differential screening, 298 and 209 clones were picked and sequenced, respectively, from the forward and reverse cDNA libraries, representing up- and down-regulated genes between the thiamethoxam-resistant and -susceptible B. tabaci .…”
Section: Introductionmentioning
confidence: 99%